ATTITUDES OF HEALTH WORKERS IN TAIWAN AND SINGAPORE TOWARDS SEXUAL MINORITY GROUPS: A SCOPING REVIEW - Sugiyani, Sugiyani; Hanifah, Yasmin Hanah; Septiana, Yesika Cahya; Lutfiah, Tarisa Azahro; Lutfinayati, Sofia; Aristawati, Tustika; Fadila, Hanifa Silmi; Lunmisay, Yulsel V; Kusumastuti, Wijayanti; Safitri, Tariza Linda; Pratiwi, Wahyu Dewi Ika; Maharani, Yasmin Cikal; Nurhidayati, Siti (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
Background: Health workers are social beings with personal perceptions and opinions about standards of sexual normality. Sexual minorities are vulnerable in accessing health services. Minority groups in Singapore are considered criminals and are not generally accepted by society and health workers such as doctors. Whereas in Taiwan, although the government has legalized same-sex marriage, minority groups still experience rejection by the community and health workers such as nurses. This is due to stigma, homophobia, and heterosexism.Objectives: Reviewing literature that discusses health workers perceptions of sexual minorities in providing health services.Methods: This scoping review used the H. Arksey & L. O'Malley framework with a journal article selection process using PRISMA. The search for journal articles used the Proquest, Pubmed, Sage Pub, Wiley, ScienceDirect, and Google Scholar databases, 21.019 articles were obtained from all databases and 3 journals were selected for analysisResults: Based on 3 selected articles with a cross-sectional study design. The results of the study revealed themes that were grouped based on the factors supporting positive attitudes and causing negative attitudes of health workers in Taiwan and Singapore towards homosexuality.Conclusion: Health workers have two different attitudes towards sexual minority groups; health workers who have a positive attitude supported by adherence to the code of ethics, level of social tolerance, and religiosity status of health workers. And health workers who have a negative attitude caused by education level and age, religious status, and socio-demographic factors.